2014
DOI: 10.15294/sji.v1i1.3638
|View full text |Cite
|
Sign up to set email alerts
|

Model Evaluasi Kesuksesan dan Penerimaan Sistem Informasi E-Learning pada Lembaga Diklat Pemerintah

Abstract: Sistem pembelajaran secara elektronik (e-learning) pada lembaga pendidikan dan pelatihan (diklat) pemerintah dibangun untuk memudahkan pegawainya dalam belajar secara on line melalui komputer di unit kerja masing- masing. Melalui sistem informasi e-learning pengguna dapat mengunduh materi diklat, mengambil dan mengumpulkan tugas-tugas, mengerjakan soal-soal ujian, melihat nilai tugas dan ujian, melihat peringkat diklat berdasarkan nilai yang diperoleh saat pelaksanaan diklat dan ikut serta dalam komunitas disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 12 publications
2
9
1
16
Order By: Relevance
“…The result of hypothesis 6 test found that satisfaction variable had a significant positive effect on attitude toward use. This study was in accordance with the result of research conducted by Rahadi (2014), Pamugar and Winarno (2014) and Kustono (2011) who also found that satisfaction had a significant effect on user performance. It could be concluded that the higher one's satisfaction in using IT, his/her motivation or tendency mentally to accept ideas in adopting and implementing a system became larger.…”
Section: The Results Of Hypothesis Testsupporting
confidence: 92%
“…The result of hypothesis 6 test found that satisfaction variable had a significant positive effect on attitude toward use. This study was in accordance with the result of research conducted by Rahadi (2014), Pamugar and Winarno (2014) and Kustono (2011) who also found that satisfaction had a significant effect on user performance. It could be concluded that the higher one's satisfaction in using IT, his/her motivation or tendency mentally to accept ideas in adopting and implementing a system became larger.…”
Section: The Results Of Hypothesis Testsupporting
confidence: 92%
“…Model UTAUT tidak dapat menilai kesuksesan sistem informasi [4]. Model kesuksesan sistem informasi Delone dan McLean sangat baik untuk menilai kesuksesan system informasi.Atas temuan-temuan tersebut maka disusunlah model penelitian seperti yang ditunjukkan pada Gambar 3.…”
Section: Gambar 3 Model Penelitianunclassified
“…Research [3] assumed that differences in organizational characteristics, business processes, organizational culture, and characteristics of the perpetrators in the organization between the government and other organizations implement IS in the government required a separate implementation method. Thus, the IS has been expected to be efficient, acceptable, and satisfying for its users and providing benefits for improving organizational performance.…”
Section: Information System Evaluationmentioning
confidence: 99%